SMAD4 Expression in Renal Cell Carcinomas Correlates With a Stem-Cell Phenotype and Poor Clinical Outcomes - Rasti, Arezoo; Madjd, Zahra; Saeednejad Zanjani, Leili; Babashah, Sadegh; Abolhasani, Maryam; Asgari, Mojgan; Mehrazma, Mitra (Frontiers in Oncology, 2021)
Renal cell carcinoma (RCC) is the most lethal neoplasm of common urologic cancers with poor prognoses. SMAD4 has a principal role in TGF-β (Transformis growth factorβ)-induced epithelial to mesenchymal transition (EMT) as a key factor in gaining cancer stem cell (CSC) features and tumor aggressiveness. This study aimed to evaluate the expression patterns and clinical significance of SMAD4 in RCC and the impact of its targeting on stem cell/mesenchymal cells and EMT characteristics in renal spheroid derived cells (SDCs) compared to parental cells (PCs) in RCC. The expression pattern and clinical significance of SMAD4 was evaluated in RCC. SDCs were enriched using a sphere culture system. Then SDCs and their PCs were compared with respect to their sphere and colony formation, expression of putative CSC markers, invasiveness as well as expression of genes, including stemness/mesenchymal, SMAD4 and TGFβ1genes. Finally, the effect of SMAD4 knockdown on SDCs was analyzed. We demonstrated that SMAD4 is positively correlated with decreased disease specific survival (DSS) in RCC patients and clear cell RCC (ccRCC) subtype and associates with poor DSS in patients with RCC, especially in ccRCC as the most metastatic RCC subtype. SDCs exhibited higher stem cell/mesenchymal properties. Inhibition of SMAD4 in PCs accelerated the dissociation of SDCs and decreased their clonogenicity, invasiveness, expression of mesenchymal markers and expression of SMAD4 and TGFβ1 genes compared to SDCs before transfection. We suggest that targeting SMAD4 may be useful against renal CSCs and may improve RCC prognosis.